Analisis Tentang Pencemaran Nama Baik dan Penyalahgunaan Hak Kebebasan Berpendapat di Media Sosial - I Made Vidi Jayananda; I Nyoman Gede Sugiartha; Made Minggu Widiantara (Jurnal Analogi Hukum, 2021)
Freedom of opinion, especially in social media, is currently widely misinterpreted and abused by the community, because in the use of the right to freedom of opinion, the community has taken many actions which fall into insult, accusations without evidence and commit defamation which cause harm to certain individuals. The problems in this research are How are criminal law regulations and violations of the abuse of the right to freedom of expression in social media and how criminal sanctions against criminal acts of defamation are under the guise of freedom of opinion. The research method used is normative legal research. Source of primary and secondary legal materials. This research concludes that freedom of opinion is not absolute freedom, but in opinion must be in accordance with ethics and norms in society and in accordance with legal regulations without harming any party.